Investment policy framework for sustainable development (UN New YorkUS, 2012)
Looks at investment policymaking, focusing on direct private investment in productive assets (i.e. excluding other capital flows), by taking a systemic approach that examines the universe of national and international policies through the lens of current key investment policy challenges. Aims to explicitly strengthen the development dimension of investment policies and presents a comprehensive Investment Policy Framework for Sustainable Development (IPFSD).
Keywords: INVESTMENT POLICY